Robust identification and characterization of thin soil layers in cone penetration data by piecewise layer optimization. (January 2022) - Cooper, Jon; Martin, Eileen R.; Yost, Kaleigh M.; Yerro, Alba; Green, Russell A.
Abstract: Cone penetration testing (CPT) is a preferred method for characterizing soil profiles for evaluating seismic liquefaction triggering potential. However, CPT has limitations in characterizing highly stratified profiles because the measured tip resistance ( q c ) of the cone penetrometer is influenced by the properties of the soils above and below the tip. This results in measured q c values that appear "blurred" at sediment layer boundaries, inhibiting our ability to characterize thinly layered strata that are potentially liquefiable. Removing this "blur" has been previously posed as a continuous optimization problem, but in some cases this methodology has been less efficacious than desired. Thus, we propose a new approach to determine the corrected q c values (i.e. values that would be measured in a stratum absent of thin-layer effects) from measured values. This new numerical optimization algorithm searches for soil profiles with a finite number of layers which can automatically be added or removed as needed. This algorithm is provided as open-source MATLAB software. It yields corrected q c values when applied to computer-simulated and calibration chamber CPT data. We compare two versions of the new algorithm that numerically optimize different functions, one of which uses a logarithm to refine fine-scale details, but which requires longer calculation times to yield improved corrected q c profiles.